KINERJA MANAJEMEN SUMBER DAYA MANUSIA DI SD INPRES ALUKME MULIA PUNCAK JAYA PAPUA TENGAH - Kogoya, Dan; Sedyastuti, Kristina; Suroso, Adi (Fakultas Ekonomika dan Bisnis Universitas PGRI Kanjuruhan Malang, 2025)
This research aims to: (1) To find out the planning and procurement of human resources at Impres Alukme Mulia Puncak Jaya Elementary School. (2) To find out the development of human resources at the Impres Alukme Mulia Puncak Jaya Elementary School, and (3) To find out how to maintain resources at the Impres Alukme Mulia Puncak Jaya Elementary School. This study uses a qualitative method with a case study type of research. The source of data from this study is the object of teachers and employees at SD Inpres Alukme Mulia Puncak Jaya, Central Papua. Primary data collection techniques are carried out through observation, interviews and documentation activities carried out in the Inpres Alukme Mulia Elementary School environment consisting of: (1) the Principal, (2) Teachers, and (3) Employees. The data analysis techniques in this study are: (1) data reduction, (2) data presentation, and (3) data verification. The results of the research are: (1) Alukme Mulia Presidential Elementary School has careful planning in the procurement of human resources. They work closely with the local Education Office to identify the needs of teaching staff and conduct a rigorous selection to recruit competent and committed teachers. (2) Human resource development in this school is focused on improving teacher competence and skills through regular training and professional development programs. and (3) Efforts to maintain human resources at SD Inpres Alukme Mulia involve the provision of welfare facilities, reward and incentive systems, a conducive work environment, effective conflict management, performance evaluation, and periodic strategy adjustments.